2011
DOI: 10.1111/j.1741-2358.2011.00539.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of mandibular implant‐retained overdentures in masticatory efficiency

Abstract: Objective: To evaluate the masticatory efficiency of patients rehabilitated with conventional dentures (CDs) or implant-retained mandibular overdentures. Background: Despite the evident benefits of implants on mastication as assessed by subjective patientbased outcomes, the extent of implant overdenture treatment effect on food comminution is not well established. Materials and methods: A randomised clinical trial was carried out with 29 completely edentulous patients divided into two groups. The first group w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 20 publications
1
28
0
1
Order By: Relevance
“…30,31 However, both studies only included patients reconstructed with vascularized bone grafts, and did not differentiate between full and partial dentures. The literature on healthy edentulous patients shows that IODs tend to be favorable to conventional dentures with regard to masticatory performance, 19,20,38 also when the mixing ability test is used as test food. 32 This discrepancy with our study is at least partially because of selection bias in favor of conventional dentures: only patients who were not satisfied with their conventional dentures either received implants or did not wear their dentures during mastication (and were therefore scored as no functional dentures).…”
Section: Masticatory Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 However, both studies only included patients reconstructed with vascularized bone grafts, and did not differentiate between full and partial dentures. The literature on healthy edentulous patients shows that IODs tend to be favorable to conventional dentures with regard to masticatory performance, 19,20,38 also when the mixing ability test is used as test food. 32 This discrepancy with our study is at least partially because of selection bias in favor of conventional dentures: only patients who were not satisfied with their conventional dentures either received implants or did not wear their dentures during mastication (and were therefore scored as no functional dentures).…”
Section: Masticatory Functionmentioning
confidence: 99%
“…Mandibular IODs offer better masticatory function and more denture satisfaction, in particular for those patients who had retention problems with their previous mandibular conventional denture. [12][13][14][15][16][17][18][19][20] Also, bite force tends to be higher in healthy patients with an IOD. [21][22][23] In addition, functioning implants may prevent further resorption of the jawbone.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13] Different methods and evaluation models have been proposed in previous studies. [14][15][16] However, the influence of denture replacement on masticatory efficiency remains. In addition, only a few studies have evaluated the influence of denture quality on patient QoL, and short-term evaluations did not reveal the significance of new dentures.…”
mentioning
confidence: 99%
“…On the other hand, responses regarding appearance and digestion were generally positive, regardless of denture type. Studies evaluating the impact on health-related QoL of the substitution of implant-supported dentures for CD show significant improvements in masticatory efficiency and QoL (Fueki et al, 2007;Farias Neto et al, 2012;Moura et al, 2016). Responses to the questionnaire employed in those studies (OHIP-EDENT) revealed a negative impact on some QoL aspects, especially physical pain, masticatory efficiency and functional limitation, matching our own findings.…”
Section: Discussionmentioning
confidence: 99%